1999
DOI: 10.1074/jbc.274.35.25093
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeleton-dependent Tyrosine Phosphorylation of the p130Cas Family Member HEF1 Downstream of the G Protein-coupled Calcitonin Receptor

Abstract: HEF1 is a recently described p130Cas -like docking protein that contains one SH3 domain and multiple SH2 binding motifs. In B cells, HEF1 is phosphorylated by a cytoskeleton-dependent mechanism that is triggered by integrin ligation. However, the induction of HEF1 phosphorylation by G protein-coupled receptors has not been reported. We found that HEF1, but not p130Cas , is tyrosine-phosphorylated following stimulation of the rabbit C1a calcitonin receptor stably expressed in HEK-293 cells. The calcitonin-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 52 publications
2
37
0
Order By: Relevance
“…41,42 PC-3M cells were grown in chamber slides, serumstarved and treated with 50 nM CT for various times (0-60 min). The cells were then processed for uPA-paxillin double immunofluorescence.…”
Section: Effect Of Ct On Redistribution Of Upa In Focal Adhesion Sitesmentioning
confidence: 99%
“…41,42 PC-3M cells were grown in chamber slides, serumstarved and treated with 50 nM CT for various times (0-60 min). The cells were then processed for uPA-paxillin double immunofluorescence.…”
Section: Effect Of Ct On Redistribution Of Upa In Focal Adhesion Sitesmentioning
confidence: 99%
“…Subsequently, the phosphorylated Cas-L regulates several signals involved in cell motility (11)(12)(13) and cell adhesion (14) as a downstream effecter of focal adhesion kinase. In addition, Cas-L functions as a signal transducer of TCR (12,15,16), BCR (17), and G protein-coupled calcitonin receptor (18). The biological functions of Cas-L in lymphocytes, however, remain to be determined.…”
mentioning
confidence: 99%
“…In addition, hItch can be recruited by the latent membrane protein 2A of Epstein-Barr virus to mediate the ubiquitination and degradation of Lyn and Syk kinase, thus down-regulating B cell signaling (32). Our studies reported here demonstrate a new role of AIP4/hItch as a ubiquitin E3 ligase for the multidomain docking protein HEF1, which has been implicated to function as an adapter protein in many signaling pathways such as those of integrin, T cell antigen receptor, and B cell antigen receptor (10,(12)(13)(14)(15). In our previous studies, HEF1 was also found to be involved in TGF-␤ signaling pathways, by interacting with Smad3, a key signal transducer in the TGF-␤ signaling pathway (7).…”
Section: Discussionmentioning
confidence: 71%
“…5C, lanes 10 -12). To test whether the ligase activity of AIP4 is necessary for such an ability of AIP4, the in vitro translated AIP4CA was added to the reaction system, as shown in lanes [13][14][15]. The ligase-dead mutant completely failed in inducing HEF1 degradation.…”
Section: The Ligase Activity Of Aip4 Is Essential For Aip4-induced Hementioning
confidence: 99%
See 1 more Smart Citation